Management of Islamic Boarding School Learning Through The Sorogan Method to Improve The Graduate Quality of Santri - Maman Suherman; Emay Mastiani; Ana Suryana; Mulyati; Rina Nuraeni (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2026)
This study aims to analyze the implementation of learning management using the sorogan method at Pondok Pesantren Nurul Iman, Bandung City, in its effort to improve graduate quality to possess intellectual depth and spiritual maturity. This research employs a qualitative approach with a descriptive case study design. Data collection was conducted through in-depth interviews, participatory observation, and documentation study, which were then analyzed using George R. Terry's management theoretical framework (POAC). The results indicate that the learning management of the sorogan method is implemented systematically through: (1) Planning based on an adaptive hierarchical curriculum; (2) Organizing based on teacher specialization (takhassus) and functional grouping; (3) Actuating emphasizing dialogical interaction and motivation through a reward system; and (4) Inherent hierarchical supervision with the Munaqasyah examination as the primary quality assurance instrument. In conclusion, the success of improving graduate quality in urban Islamic boarding schools lies in the rigorous integration of Salaf tradition standards with modern managerial flexibility. Keywords: Learning Management, Sorogan Method, Graduate Quality. Abstrak: Penelitian ini bertujuan untuk menganalisis implementasi manajemen pembelajaran metode sorogan di Pondok Pesantren Nurul Iman, Kota Bandung, dalam upayanya meningkatkan mutu lulusan agar memiliki kedalaman intelektual dan kematangan spiritual. Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus deskriptif. Pengumpulan data dilakukan melalui wawancara mendalam, observasi partisipatif, dan studi dokumentasi, yang kemudian dianalisis menggunakan kerangka teori manajemen George R. Terry (POAC). Hasil penelitian menunjukkan bahwa manajemen pembelajaran metode sorogan diterapkan secara sistematis melalui: (1) Perencanaan berbasis hierarki kurikulum yang adaptif; (2) Pengorganisasian berbasis spesialisasi keahlian ustadz (takhassus) dan pengelompokan fungsional; (3) Pelaksanaan yang menekankan interaksi dialogis dan motivasi melalui sistem reward; serta (4) Pengawasan melekat berjenjang dengan ujian Munaqasyah sebagai instrumen penjamin mutu utama. Kesimpulannya, keberhasilan peningkatan mutu lulusan di pesantren urban terletak pada integrasi ketatnya standar tradisi salaf dengan fleksibilitas manajerial modern. Kata Kunci: Manajemen Pembelajaran, Metode Sorogan, Mutu Lulusan.